Structural Systems for Modern Architecture in Iraq Analysis Study to Dr. Qahtan Al-Madfa’i’s Architecture (Journal of Engineering, 2015)
Dr. Qahtan Al-Madfa’i’s architecture has been characterized by a particular characteristic that may be unique and extreme at the same time, that is the use of the distinctive three-dimensional structural coverings and the exploitation of structural construction to give an extra aesthetic touch to the composition of the building, to achieve the application of his universal ideas, which he strongly believed and defended.      In the period of the marked urban decline that the country undergoes now, which urges us toward making a comparison between the beginning of the modern Iraqi architecture and its ascending path up to its peak and the periods of its decline until it reached a very bad condition which has been referred to by many critics and specialists. In order not to have solutions that are subject to action-and-reaction principle, it is necessary to search for the intact origins of this architecture and its construction, define its concepts and achievements and the methods adopted by its pioneers to scaffold the urban status of Iraq and to find a pure Iraqi touch full of modernity and innovation. Dr. Qahtan Al-Madfa’i is one of those distinguished pioneers whose works and urban outcome can take as excellent examples of that period and to deduce from him and from his work many things that cannot be ignored.       All of this will be done through the illustration and analysis of selected group of Al-Madfa’i’s buildings, designed and implemented, and to be compared with the works of his international architects and thereby reaching the goal of the research.